Association between baseline VEGF/sVEGFR-2 and VEGF/TSP-1 ratios and response to metronomic chemotherapy using cyclophosphamide and celecoxib in patients with advanced breast cancer - Perroud, Herman A (2013)
Fil: Fil: Perroud, Herman A. Institute of Experimental Genetics. School of Medical Sciences. National University of Rosario; Rosario; Argentina